Ali lahko z modeli napovemo usodo zdravila v telesu in optimiramo zdravljenje? - Bogataj, Marija (Farmacevtski vestnik, 2020)
In this article, the principle of biopharmaceutical processes is pursued: dissolution, absorption, distribution, metabolism and elimination. For the evaluation of these processes we use different models. First we describe the models used to evaluate drug dissolution in vitro and the models used to estimate absorption and permeability in vitro. The information thus obtained can be used to classify drugs according to the biopharmaceutical classification system and to predict the extent of their absorption. Then, the models for the evaluation of metabolism and the principles of pharmacokinetic-pharmacodynamic modelling are described. The basic goal of studying pharmacokinetic processes is to optimise the pharmacotherapy of patients, which can be in clinical practice further upgraded with clinical pharmacy services.
Keywords: bioanalitika; biofarmacija; farmakokinetični procesi; Farmakokinetika; Klinična farmacija; modeli; procesi sproščanja